Public Works Programs and Crime : Evidence for El Salvador - Acosta, Pablo; Monsalve Montiel, Emma (World Bank, Washington, DC, 2018)
Most evaluations of public works programs in developing countries study their effects on poverty reduction and other labor market outcomes (job creation, earnings, and participation). However, very few look at other collateral effects, such as the incidence of violence. Between 2009 and 2014, El Salvador implemented the Temporary Income Support Program, which aimed to guarantee a temporary minimum level of income to extremely poor urban families for six months, as well as provide beneficiaries with experience in social and productive activities at the municipal level. Making use of a panel data set at the municipal level for 2007 to 2014, with monthly data on different types of crime rates and social program benefits by municipalities, this paper assesses the effects of the program on crime rates in municipalities in El Salvador. There are several possible channels through which the Temporary Income Support Program can affect crime. Since the program is associated with cash transfers to beneficiaries, a reduction in economically motivated crimes is expected (income effect). But since the program enforces work requirements and community participation, this could generate a negative impact on crime, because the beneficiaries will have less time to commit crime and because of community deterrence effects. Overall, the paper finds a robust and significant negative impact of the Temporary Income Support Program on most types of crimes in the municipalities with the intervention. Moreover, the negative effects of the program on some types of crime rates hold several years after participation. Positive spillover effects for municipalities hold within a radius of 50 kilometers.